The Needs of Carers in the Eating Disorders Setting and How Nurses can Help - Smillie, Amanda (2014)
Abstract Carers of people with an eating disorder describe feelings of stress, anxiety, isolation and hopelessness. This then leads them to experience ill health and poor wellbeing. The study looks at the experience of caring for a loved one with an eating disorder from a carer’s perspective. It also examines interventions that helped carers during this time and what would have been beneficial to them to enhance their own health and wellbeing. Five participants were recruited from eating disorder’s charities that provide help and support to carers. Semi-structured interviews were conducted. Analysis of the data found that carers felt their needs were secondary to their loved ones and that love acted as a motivator for them to carry on caring. Recommendations for nursing practice include more education regarding carer’s needs to improve awareness of this issue and to prevent ill health. Family-Centred care approaches, commonly seen within children’s services, should be adopted in order for carers to be involved in the care of their loved ones. Also the development of a role within teams to act as a “Carer Specialist Nurse” would be useful in order to promote health and wellbeing.